Caring Interventions for the Most Vulnerable Populations in Economically Disadvantaged Areas during the Coronavirus (COVID-19) Pandemic by Non-Governmental Organizations in Kenya - Solymári, Daniel; Kairu, Edward; Czirják, Ráhel; Tarrósy, István (Social sciences (Basel), 2023)
This paper deals with COVID-19-hit Kenyan slums and the numerous interventions civil society organizations implemented during the first waves of the pandemic since it was initially detected in March 2020. As part of a comprehensive project using mixed methodology, including desk research and key informant interviews, community-based organizations and non-governmental organizations, together with other stakeholders of their collaborative networks, were investigated regarding the roles that they played, the projects they carried out, and the interventions they were involved in in the mitigation of the negative impacts of COVID-19. This paper investigates how COVID-19 actually hit Kenyan slums and how it affected civil society organizations during the pandemic.